1996
DOI: 10.1038/383254a0
|View full text |Cite
|
Sign up to set email alerts
|

Functional anatomy of a common semantic system for words and pictures

Abstract: The relationship between the semantic processing of words and of pictures is a matter of debate among cognitive scientists. We studied the functional anatomy of such processing by using positron-emission tomography (PET). We contrasted activity during two semantic tasks (probing knowledge of associations between concepts, and knowledge of the visual attributes of these concepts) and a baseline task (discrimination of physical stimulus size), performed either with words or with pictures. Modality-specific activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

102
619
6
6

Year Published

1997
1997
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,095 publications
(733 citation statements)
references
References 25 publications
102
619
6
6
Order By: Relevance
“…Previous studies investigating the left occipitotemporal cortex have indicated the existence of a hierarchy for visual word processing, progressing from simple letter percept in the occipital cortex to more complex features in the anterior inferior temporal regions (e.g., (Fernandez et al, 2001;Hagoort et al, 1999;Vandenberghe et al, 1996). More recently, a posterior to anterior VWF-System gradient of increasing print specificity was found in adults and adolescents (Brem et al, 2006;Vinckier et al, 2007) as well as in children (Brem et al, 2009;Van der Mark et al, 2009).…”
mentioning
confidence: 99%
“…Previous studies investigating the left occipitotemporal cortex have indicated the existence of a hierarchy for visual word processing, progressing from simple letter percept in the occipital cortex to more complex features in the anterior inferior temporal regions (e.g., (Fernandez et al, 2001;Hagoort et al, 1999;Vandenberghe et al, 1996). More recently, a posterior to anterior VWF-System gradient of increasing print specificity was found in adults and adolescents (Brem et al, 2006;Vinckier et al, 2007) as well as in children (Brem et al, 2009;Van der Mark et al, 2009).…”
mentioning
confidence: 99%
“…Most of these studies, however, have focused on the distinction between different types of materials (i.e., verbal vs nonverbal), presented through the visual (Bright et al, 2004;Moore and Price, 1999;Vandenberghe et al, 1996;Vandenbulcke et al, 2006) and auditory (Dick et al, 2007;Thierry et al, 2003;Visser and Lambon Ralph, 2011) modalities. It is clear that the inferential versus referential distinction does not exactly map onto the verbal-nonverbal distinction.…”
Section: Spared Referential Impaired Inferential Processingmentioning
confidence: 99%
“…Following this distinction, several studies have highlighted, in addition to a common left lateralized semantic network, material-specific activations, involving left hemispheric regions for verbal stimuli and right hemispheric regions for nonverbal stimuli (Thierry et al, 2003;Thierry and Price, 2006;Vandenberghe et al, 1996 as reanalyzed by Thierry and Price, 2006;Vandenbulcke et al, 2006). Specifically, some authors found that left middle and superior temporal regions were selectively more involved for verbal material, while the right midfusiform and right posterior middle temporal cortex were selectively more involved for nonverbal processing (Thierry and Price, 2006;Vandenberghe et al, 1996 as in Thierry and Price, 2006; and for converging evidence in patients with neurodegenerative pathologies see Butler et al, 2009).…”
Section: Spared Referential Impaired Inferential Processingmentioning
confidence: 99%
See 2 more Smart Citations